Determinant Factors of Forming Individual Tacit’s Knowledge: Teachers’ Experience Perspective - Dewi, Laksmi; Setiawan, Budi; Hernawan, Asep Herry; Sukirman, Dadang; Khoirunnisa, Azizah Nurul; Arwan, Juwintar Febriani (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the factors influencing the exchange of tacit knowledge among teachers, which supports creativity, learning, and problem-solving in education. It focuses on how individual knowledge and the sharing of tacit knowledge are interconnected. The research examines four key factors: teaching experience (including education level and attitude), length of service, socialization, and training, and attitudes toward the Freedom of Learning Curriculum. A quantitative survey method was used to collect data from 123 vocational high school teachers between June 21-23, 2023. The participants were asked to complete an online questionnaire about their background and attitudes toward curriculum changes. Descriptive and inferential statistical analyses were applied to the data. The results show that teachers' experience-based knowledge is a crucial factor in acquiring and sharing tacit knowledge, which fosters human connections and collaboration. The findings also reveal that teachers' personal experiences and interactions play a key role in the exchange of unspoken knowledge, leading to improved relationships between teachers and students and expanding their social networks.